Dietary supplement use, perceptions, and associated lifestyle behaviors in undergraduate college students, student-athletes, and ROTC cadets. Issue 2 (17th February 2018) - Valentine, Arthur A.; Schumacher, Julie Raeder; Murphy, Jan; Ma, Yoon Jin
ABSTRACT: Objective : To identify the prevalence of dietary supplement (DS) use, perceptions of DS efficacy, and lifestyle behaviors of DS users and non-users.Participants : Undergraduate students, student-athletes, and ROTC cadets at a Midwestern University between September 2014 and January 2015.Methods : A cross-sectional online survey was administered. Analysis included descriptive statistics, chi-square, and independent sample t-tests.Results : At least 50% of respondents from each group reported DS use. Users generally reported favorable perceptions of efficacy. Undergraduate student DS users reported more exercise and more healthful dietary habits compared to non-users; however, nearly 72% of undergraduates who reported tobacco use also reported DS use. Less significant differences were observed in the student-athlete and cadet samples.Conclusions : DS use is common on college campuses, and many DS users report favorable perceptions of efficacy. With the exception of tobacco use, collegiate DS users generally report lifestyles that are as healthy or healthier than non-users.